Effect of Supply Chain Cultural Competence on Thai SMEs Performance with Mediating Role of Supply Chain Technology - Mekhum, Witthaya (International Journal of Supply Chain Management, 2020)
Performance is a key indicator for the survival of any business. Organizational culture must have strong liaison with the goals of organizations because it has direct association with organizational performance. Therefore, the core objective of this study was to investigate the influence of supply chain cultural capabilities on the performance of Thai SMEs with the mediation role of supply chain technology adoption. To achieve the objective of this study, the data was collected from the managers of SMEs by using survey questioner approach. Smart-PLS was used to test the hypotheses and analysis of data. Findings of contemporary study highlighted that supply chain cultural capabilities have significant positive influence on the performance of SMEs in Thailand. Furthermore, results indicated that supply chain technology adoption could increase the performance of organizations. Results of this research illuminated that Adaptability and consistency in organizational cultural support in the adoption of supply chain technology and supply chain technology boost up the performance of organization. This research offer new empirical indication that supply chain cultural capabilities are significant for the performance of SMEs in developing countries like Thailand. Though, this research used only cultural capabilities, the other important capabilities of supply chain such as supply chain technological capabilities, would be used in future research.